ECG-based estimation of dispersion of APD restitution as a tool to stratify sotalol-induced arrhythmic risk. - Mincholé, A; Bueno-Orovio, A; Laguna, P; Pueyo, E; Rodriguez, B (Elsevier, 2015)
Background: Increased spatial dispersion of restitution properties has been associated to arrhythmic risk. An ECG-based index quantifying restitution dispersion, DRest, is evaluated in patients who experienced Torsades de Pointes (TdP) under sotalol challenge and compared with the response in healthy subjects. Methods and Results: ECG recordings were analyzed for quantification of DRest and QTc, among others biomarkers. DRest provides improved discrimination following sotalol administration between TdP and healthy subjects ([min–max]: [0.18–0.22] vs [0.02–0.12]), compared to other biomarkers including QTc ([436–548 ms] vs [376–467 ms]). Results in healthy subjects are in agreement with simulations of sotalol effects on a human tissue electrophysiological model. Conclusions: This case study supports the potential of DRest for improved arrhythmia risk stratification even with QTc values below 450 ms.